2021
DOI: 10.1155/2021/8877567
|View full text |Cite
|
Sign up to set email alerts
|

Postradiation Fractures after Combined Modality Treatment in Extremity Soft Tissue Sarcomas

Abstract: Soft tissue sarcoma (STS) of the extremities is typically treated with limb-sparing surgery and radiation therapy; with this treatment approach, high local control rates can be achieved. However, postradiation bone fractures, fractures occurring in the prior radiation field with minimal or no trauma, are a serious late complication that occurs in 2–22% of patients who receive surgery and radiation for STS. Multiple risk factors for sustaining a postradiation fracture exist, including high radiation dose, femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Lower extremity (LE) sarcomas, in particular, are associated with an increased risk of surgical complications compared to tumors located within the upper extremity 12,13 . In addition, prior studies have found that the use of radiation therapy in the perioperative period can further increase the incidence of complications seen in this patient population 14–16 . Unfortunately, the lower limb is also the most common location in which soft tissue sarcomas arise 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower extremity (LE) sarcomas, in particular, are associated with an increased risk of surgical complications compared to tumors located within the upper extremity 12,13 . In addition, prior studies have found that the use of radiation therapy in the perioperative period can further increase the incidence of complications seen in this patient population 14–16 . Unfortunately, the lower limb is also the most common location in which soft tissue sarcomas arise 12 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, prior studies have found that the use of radiation therapy in the perioperative period can further increase the incidence of complications seen in this patient population. [14][15][16] Unfortunately, the lower limb is also the most common location in which soft tissue sarcomas arise. 12 The purpose of our study is to comprehensively investigate risk factors predisposing to postoperative complications following limb-sparing, LE sarcoma surgery.…”
mentioning
confidence: 99%
“…There were multiple early complications secondary to wound healing complications. While radiation therapy improves rates of local control, it is not a benign intervention and is associated with the complications observed in our study [ 4 , 32 , 33 , 34 , 35 ]. Although consideration for postoperative radiotherapy can be given, the permanent functional complications of stiffness and fibrosis, especially around joints, occur secondary to the higher treatment doses and volumes [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 83%
“…For example, postradiation fractures have been reported with an incidence of 1.2–6.4% and with well-established risk factors [ 33 ]. These fractures can occur without significant trauma due to changes in the mechanical strength of the bone after irradiation [ 34 ]. In our study, eight patients (4.0%) experienced pathological fractures, and five of them were managed as ORN based on the clinical history, imaging, and assessment of soft tissue quality.…”
Section: Discussionmentioning
confidence: 99%